Implementation of Corporate Social Responsibility (CSR) and Its Impact on the Economy, Social, and Community Environment after the Covid-19 Pandemic at PT Angkasa Pura I I Gusti Ngurah Rai International Airport, Bali - Made Riska Kusumadewi; Kadek Dwi Cahaya Putra; Putu Adriani Prayustika (Jipmor: Jurnal Ilmu Pendidikan Dan Humaniora, 2024)
This study aimed to determine the implementation of Corporate Social Responsibility (CSR) at PT Angkasa Pura I I Gusti Ngurah Rai International Airport Bali and its economic, social and environmental impacts on society after the Covid-19 pandemic. Data analysis techniques include data collection, condensation, presentation, and conclusion. The analytical method uses descriptive qualitative. The results of this study show that the implementation of CSR after the Covid-19 pandemic is still the same in the planning process, and differences occur in the amount and target of assistance. The impact of the program uses the Theory of Change (ToC) using inputs (money, labor, time), then outcomes in the form of economic, social and environmental impacts, as well as impacts felt by the community, namely the economic impact of increasing income, the social impact of increasing school education facilities, and the environmental impact that has not been fully felt from the results of the assistance that has been mutually agreed upon. To receive a positive impact from the community in the long term, it is necessary to have program impact management and transparency of distribution data every year of distribution.